Object center of mass predicts pointing endpoints in virtual reality - Schuetz, Immo; Fiehler, Katja (Frontiers in Virtual Reality, 2024)
Humans point using their index finger to intuitively communicate distant locations to others. This requires the human sensorimotor system to select an appropriate target location to guide the hand movement. Mid-air pointing gestures have been well studied using small and well defined targets, e.g. numbers on a wall, but how we select a specific location on a more extended 3D object is currently less well understood. In this study, participants pointed at custom 3D objects ("vases") from different vantage points in virtual reality, allowing to estimate 3D pointing and gaze endpoints. Endpoints were best predicted by an object's center of mass (CoM). Manipulating object meshes to shift the CoM induced corresponding shifts in pointing as well as gaze endpoints, suggesting that CoM plays a major role in guiding eye-hand alignment, at least when pointing to 3D objects in a virtual environment.